2009
DOI: 10.3892/ijo_00000209
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hedgehog signaling pathway in proliferation and invasiveness of hepatocellular carcinoma cells

Abstract: Abstract. The Hedgehog (Hh) pathway has been confirmed a contributor to the carcinogenesis and progression of various tumor types. To investigate the Hh signaling activity in human hepatocellular carcinoma (HCC), we detected the expression levels of Hh pathway components (Shh, Ptch1 and Gli2) in 57 samples of HCC and corresponding adjacent-tumor liver tissues. The Hh pathway was overexpressed in cancer tissues compared with non-cancer tissues and correlated closely with histologic differentiation and portal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Additional mechanisms of aberrant pathway activation can be ligand-dependent, autocrine activation of the pathway, whereby cancer cells can upregulate the synthesis of the Shh ligand and stimulate Hh/GLI pathway activation. This type of pathway activation is common in prostate cancer, hepatocellular carcinoma, pancreatic cancer, and non-small cell lung cancer [ 236 , 237 , 238 , 239 , 240 ]. The Shh ligand can also be secreted by tumor cells and can participate in paracrine signaling, activating the Hh/GLI signaling pathway in both tumor and stromal cells, often seen in pancreatic and prostate cancers [ 34 , 235 , 241 , 242 ].…”
Section: The Hh/gli Signaling Pathway In Diseasementioning
confidence: 99%
“…Additional mechanisms of aberrant pathway activation can be ligand-dependent, autocrine activation of the pathway, whereby cancer cells can upregulate the synthesis of the Shh ligand and stimulate Hh/GLI pathway activation. This type of pathway activation is common in prostate cancer, hepatocellular carcinoma, pancreatic cancer, and non-small cell lung cancer [ 236 , 237 , 238 , 239 , 240 ]. The Shh ligand can also be secreted by tumor cells and can participate in paracrine signaling, activating the Hh/GLI signaling pathway in both tumor and stromal cells, often seen in pancreatic and prostate cancers [ 34 , 235 , 241 , 242 ].…”
Section: The Hh/gli Signaling Pathway In Diseasementioning
confidence: 99%
“…The SHH signaling pathway (SHH) plays a pivotal role in the proliferation and invasiveness of HCC cells [ 48 , 49 , 50 , 51 , 52 ]. The activation of the SHH signaling pathway occurs after the HH ligand binds to its receptor Patched1 (PTCH1) [ 51 , 52 ].…”
Section: Signaling Pathways Involved In Cancer Stem Cells Of Hccmentioning
confidence: 99%
“…Although there is no universal CSC marker that can be used to identify the CSCs of HCC, studies have shown some of the main surface markers that can identify liver CSCs, including epithelial cell adhesion/activating molecule (EpCAM) (CD326), cluster of differentiation 90 (CD90), CD44 and CD133 [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The reported main molecular signaling pathways attending the pathogenesis of the CSCs of HCC include the Wnt/β-catenin, transforming growth factors-β (TGF-β), sonic hedgehog (SHH), PI3K/Akt/mTOR and Notch pathways [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Introductionmentioning
confidence: 99%
“…The SMO inhibitor cyclopamine has been shown to reduce DNA synthesis, resulting in inhibition of the cell growth, invasiveness, and motility of HCC cells [ 78 ]. In addition, cyclopamine suppresses cell viability and increases apoptosis after downregulating Bcl-2 in HCC cells [ 73 ].…”
Section: Smo and Liver Cancermentioning
confidence: 99%